ANALISIS KETERCAKUPAN BUKU IPA BSE SD KELAS 3 - Achmad Fanani; Triman Yuniarso (LPPM Universitas PGRI Adi Buana Surabaya, 2013)
This research aims to analyze the third grade science elementary BSEtext book’s embracement materials to meet a demand of the basic competencies.The problems of this research are about how the third grade science elementaryBSE text book’s embracement materials can meet a demand of the basiccompetencies. Those problems are listed into (the embracement, thoughtful thecontexts, the difficulty level, the topic materials organization and the validity) ofthe concepts which are given in the third grade science elementary BSE text book.The current results conclude that the range of material embracementfulfills the material substances which applied in the competency’s standard andthe basic competency that are already arranged by the regulation of NationalMinistry of Education number 22 year 2006 about the content’s standards.Materials in each topic contain a worksheet for helping appreciate the learningprocess and there a repeating to further understanding.The difficulty level of the third grade science elementary BSE text book ofS. Rositawati, Aris Muharam already meets the level of thinking maturity and thesocial emotional of students. Language description which used to explain conceptor applicative illustration and how to describe a defined example are good enough.Sentences that used are communicative enough with the illustrated whichexplain the concepts from closest environment to the global environment. Theorganization and the layout systematic in each chapter meet the laws andsystematically, contain preface, content and closing. The layout are suitable withthe deductive concepts (general into specific) or deductive (specific into general),start from the easiest to the most difficult, from the exact into abstract, and fromthe simplest into the complex, from the well-known into unknown. There somemisconceptions which are found with definition correlation, explanation indescription and applied examples.